1997
DOI: 10.1007/s002329900158
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene D 4 -induced Ca 2+ Mobilization in Ehrlich Ascites Tumor Cells

Abstract: Stimulation of Ehrlich ascites tumor cells with leukotriene D4 (LTD4) within the concentration range 1-100 nm leads to a concentration-dependent, transient increase in the intracellular, free Ca2+ concentration, [Ca2+]i. The Ca2+ peak time, i.e., the time between addition of LTD4 and the highest measured [Ca2+]i value, is in the range 0.20 to 0.21 min in ten out of fourteen independent experiments. After addition of a saturating concentration of LTD4 (100 nm), the highest measured increase in [Ca2+]i in Ehrlic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 24 publications
3
12
0
Order By: Relevance
“…These results are in keeping with previous results using HEK-293 cells expressing the CysLT 1 receptor [9] and human neutrophils [5], which showed that most of the response (>80%) persisted after removing extracellular calcium. Furthermore, in agreement with previous results with DMSO-differentiated HL-60 cells [32] and human neutrophils [5] [32,33], almost exclusive release from intracellular stores [5], or both [34].…”
Section: Discussionsupporting
confidence: 93%
“…These results are in keeping with previous results using HEK-293 cells expressing the CysLT 1 receptor [9] and human neutrophils [5], which showed that most of the response (>80%) persisted after removing extracellular calcium. Furthermore, in agreement with previous results with DMSO-differentiated HL-60 cells [32] and human neutrophils [5] [32,33], almost exclusive release from intracellular stores [5], or both [34].…”
Section: Discussionsupporting
confidence: 93%
“…In rat hepatocytes, LTD 4 activates both Ca 2+ -dependent and Ca 2+ -independent anion conductances, whereas direct application of 100 nM LTD 4 in neuroblastoma cells [61] or 5 nM LTD 4 in EATC [41,62] failed to elicit efflux/currents. An increased Cl --permeability has previously been described after addition of 100 nM LTD 4 to EATC [63], but since this concentration of LTD 4 is known to increase [Ca 2+ ] i in EATC [64], it is likely that this permeability increase represents activation of I Cl,Ca . LTD 4 also failed to induce activation of a Cl --conductance in several other cell types tested [25,65].…”
Section: Arachidonic Acid and Eicosanoidsmentioning
confidence: 97%
“…LTD 4 binds to CysLT receptors, of which the human CysLT 1 [119,120], the human CysLT 2 (Gene Bank accession number BAB03601) and the murine CysLT 1 [121] are cloned. Binding of LTD 4 to the receptor results in Ca 2+ release and Ca 2+ influx in EATC cells [63,64] and in many other cell types (see e.g. [122] [62], and addition of LTD 4 decreases the activation time of I K,vol [62]; (vi) the single-channel conductance of the LTD 4 -activated channel is approximately 5 pS, as estimated from non-stationary noise analysis [126] similar to that found for I K,vol .…”
Section: Eicosanoidsmentioning
confidence: 99%
“…In human detrusor smooth muscle cells, it was reported that elevation in [Ca 2ϩ ] i levels evoked by LTD 4 were almost exclusively due to mobilization from intracellular Ca 2ϩ stores (4). In other target cells, the LTD 4 -evoked Ca 2ϩ response was dependent on the release of Ca 2ϩ from intracellular stores and enhanced Ca 2ϩ influx (20,23). The present study demonstrates that both ANG II-and CysLTevoked increases in [Ca 2ϩ ] i levels were significantly attenuated by 2-APB.…”
Section: Discussionmentioning
confidence: 99%
“…They exert their actions via activation of at least two pharmacologically defined G proteincoupled receptors (CysLT 1 and CysLT 2 ) that are linked to PLC-mediated Ca 2ϩ mobilization (8,16). In addition to their well-known bronchiolar smooth muscle spasmogenic effect, these inflammatory mediators have been shown to enhance contractile responses in smooth muscle preparations or [Ca 2ϩ ] i levels in their target cells (4,10,20,21,23,29,30). Recently, with the use of a variety of techniques including in situ hybridization, Northern blotting, and RT-PCR, the presence of CysLT 1 and/or CysLT 2 transcripts in cardiac tissue has been identified (8,10,16,21).…”
Section: -Lipoxygenase (5-lo) or 3-[[[3-[2-(7-chloro-2-quinlinyl)ethmentioning
confidence: 99%